A space for grace towards an aesthetics of preaching - Cilliers, Johan 1954- (Stellenbosch SUN PRESS, 2016)
IN SEARCH OF SPACE: Sermon: "Lord, let us build a home for you ..." (Mark 9:2-8) -- A SPACE CALLED HOME: Sermon: A home called desert (Genesis 21:1-21) -- A SPCAE FOR HEARING: Sermon: "There is the lamb of God ..." (John 1:19-34) -- INTERLUDE: THE SOUND OF MUSIC: Sermon: Duet from the depths (Acts 16:16-34) -- A SPACE FOR SEEING: Sermon: The spiral of goodness (Romans 12:9-21) -- A SPACE FOR TOUCHING, TASTING, SMELLING: Sermon: Curious kurios (John 13:1-17) -- TIMELESS TIME AND PLACELESS SPACE?: Sermon: It is time (2 Corinthians 6:1-2)
Keywords: Preaching; Sermons, English; Space and time; Preaching; Sermons, English; Space and time